The colonizing self : or, home and homelessness in Israel/Palestine - Kotef, Hagar, 1977- (Theory in forms., 2020)
"The Colonizing Self examines practices of homemaking in Israel/Palestine to understand how people develop attachments to spaces of violence and how they consequently become willful participants in state violence. The author explores the cultural, political, spatial, and theoretical apparatuses that enable people and nations to construct a home on the ruins of other people's homes or to feel that they belong to spaces of dispossession. Through these lenses, it examines the affectual conditions of possibility of settler colonialism: the mechanisms of attachments and political belonging that work to allow settling-down when the act of settlement is also an act of destruction"--